Innovations in Computer Science and Engineering Proceedings of the Fourth ICICSE 2016 - Saini, H. S.; Sayal, Rishi; Rawat, Sandeep Singh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book is a collection of high-quality peer-reviewed research papers presented at the Fourth International Conference on Innovations in Computer Science and Engineering (ICICSE 2016) held at Guru Nanak Institutions, Hyderabad, India during 22 - 23 July 2016. The book discusses a wide variety of industrial, engineering and scientific applications of the emerging techniques. Researchers from academic and industry present their original work and exchange ideas, information, techniques and applications in the field of data science and analytics, artificial intelligence and expert systems, mobility, cloud computing, network security, and emerging technologies.
Preface -- A Note From the Organising Committee -- Organising Committee -- About the editors -- Table of Contents -- Chapters -- Subject Index -- Author Index.
Keywords: Telecommunication; Data protection; Computational intelligence; Communications Engineering, Networks; Data and Information Security; Computational Intelligence